Legal Review of the Role of Village Government in Village Development under Law Number 3 of 2024 on the Second Amendment to Law Number 6 of 2014 on Villages - La Ode Siraga; L.M. Ricard Zeldi Putra; Wa Ode Novita Ayu Muthmainna (AIQU: Journal Multidiscipliner of Science, 2025)
This research is motivated by the fact that Molona Village remains categorized as an underdeveloped village. This situation illustrates that development in Molona Village, South Buton Regency, still faces numerous challenges and obstacles. Therefore, this research can be formulated as follows: 1. What is the role of the village government in village development in Molona Village, from the perspective of Law Number 3 of 2024 concerning the Second Amendment to Law Number 6 of 2014 concerning Villages? 2. What are the factors hindering the role of the village government in village development in Molona Village, South Buton Regency? This study aims to determine the role of the Molona Village Government, South Buton Regency, in village development, and the factors that hinder the Molona Village Government, South Buton Regency, in carrying out village development. This study uses empirical legal research, with data collection consisting of observation, interviews, and documentation. The resource person for this study was Mr. La Ode Mustafa, the Head of Molona Village, South Buton Regency. Data analysis used qualitative analysis techniques, namely the interpretation of data by providing explanations and descriptions. The results of the study indicate that the Molona Village Government, South Buton Regency, plays a crucial role in supporting village development. The Molona Village Government's role in village development begins with its role as a development planner, its role as an implementer, and its role as a monitor and supervisor of every program or activity aimed at developing Molona Village. This study also found that the main inhibiting factors for the Molona Village Government in carrying out village development are the low level of education of the village community and the lack of participation of the village community in the village development process.